The Cytoplasmic Tail of Glycoprotein M (gpUL100) Expresses Trafficking Signals Required for Human Cytomegalovirus Assembly and Replication - Krzyzaniak, Magdalena (American Society for Microbiology, 2007)
The virion envelope of human cytomegalovirus (HCMV) is complex and consists of an incompletely defined number of glycoproteins. The gM/gN protein complex is the most abundant protein component of the envelope. Studies have indicated that deletion of the viral gene encoding either gM or gN is a lethal mutation. Analysis of the amino acid sequence of gM disclosed a C-terminal acidic cluster of amino acids and a tyrosine-containing trafficking motif, both of which are well-described trafficking/sorting signals in the cellular secretory pathway. To investigate the roles of these signals in the trafficking of the gM/gN complex during virus assembly, we made a series of gM (UL100 open reading frame) mutants in the AD169 strain of HCMV. Mutant viruses that lacked the entire C-terminal cytoplasmic tail of gM were not viable, suggesting that the cytoplasmic tail of gM is essential for virus replication. In addition, the gM mutant protein lacking the cytoplasmic domain exhibited decreased protein stability. Mutant viruses with a deletion of the acidic cluster or alanine substitutions in tyrosine-based motifs were viable but exhibited a replication-impaired phenotype suggestive of a defect in virion assembly. Analysis of these mutant gMs using static immunofluorescence and fluorescence recovery after photobleaching demonstrated delayed kinetics of intracellular localization of the gM/gN protein to the virus assembly compartment compared to the wild-type protein. These data suggest an important role of the glycoprotein gM during virus assembly, particularly in the dynamics of gM trafficking during viral-particle assembly.